CONCEPT OF BEAUTY THROUGH AYURVEDA - *Saurabh Deshmukh; Khushal Nikhode; Trupti Thakre; Mayuri Talnikar (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda is an ancient medical science which was developed in India. Ayurveda deals with all the aspects of human life. Since early age, human life has a great impact on the external appearance of oneself. Skin is the basic element of the external appearance. Beauty is generally depended on the type and texture of the skin one has. Also the beauty is not only depended on the skin but also on the other factors like hair falling, hair blackening, wrinkle free skin etc. In todays era, beauty is very much essential to be one in thousand faces. It is essential for the preservation, restoration or bestowing of bodily beauty and also in the surgical correction of disfigured physical defects. Beauty as in common is related to skin unanimously. Beautiful skin of person gives perceptual experience of satisfaction. Ayurvedic science deals with cosmetology in a very precise way. Cosmetics drugs is widely been described as Varnya, Kustaghna, Kandughna, Vayasthapak, etc. Some medicinal plants like- Haridra, Manjistha, Sariva, Chandana, Amalaki, Ghritkumari, Babul, Lavanga, Shikakai, Ritha, Bhringaraj etc. has been prescribed for beautification of skin, hair, etc. Diet has a special role to improve and maintain beauty of an individual. Panchakarma procedures and Rasayanas are employed for beatification of skin, the marker of overall condition of individual as per Ayurveda.